Some Reflections on Bobrow’s Counterpoint to Walach’s Review - Walach, Harald (Journal of Scientific Exploration, 2022)
I am grateful for Robert S. Bobrow’s “Counterpoint”. Discourse and controversy are essential elements, both of science and of finding political consensus. Both have suffered immensely over the last two years. And in my view, this has to do with the subtle mechanisms of censoring installed. Dissenting voices are silenced, in the media and in academia. Political opinion is no longer a free, consensus seeking debate. All is put under the umbrella of “unity for fighting the pandemic”. I think the way one can read Kennedy’s book, my review of it, and Bobrow’s comments hinges on two central questions. I am not going to answer them, but I wish to raise them for discussion. I will give a few bits of my opinion and my reasons for it. The first question is: Is it true that we were faced with a “pandemic”, i.e,. a worldwide, devastating infectious disease problem? The second question is: Can we really trust our institutions, i.e. the political executive (in the US the president and his administration, in Germany our chancellor and its executive ministry), our media, our parliamentary democracy? Depending on your own answer to these questions, you will find both my review and Kennedy’s book annoying or helpful. Bobrow obviously answers both questions in the positive. I would agree with him: Vaccinations have done a lot of good, especially in the case of polio. But, following some studies and reports relayed by Kennedy, the recent polio vaccination campaigns in India and Africa have led to more unwanted effects than benefits and were stopped by the governments for that reason. That might have been completely different in the 60ies, when polio was a real threat. But one fact, easily overlooked, likely not so relevant for polio, but for other diseases is: all infectious diseases were on a steep decline many years before vaccines became available. That vaccines might have accelerated the decline is likely. Had we not found any vaccines, we might have seen the same decline, only a bit slower. This argument is old and was made, to my knowledge, first by McKeown (McKeown, 1976). But the point is, Covid-19 vaccines are not vaccines. But let me get back to that argument later. Back to our central questions: I was, by and large, of the opinion that our institutions function well. Until I started to read a bit more widely in political texts, media literature and critical social analysis. For instance, reading well researched books like Sands (2020); Sutton (1976); Talbot (2015) gives you some taste of underground politics where quite some background forces are at work that steer the seemingly benevolent forces of visible political actors toward the agenda of powerful elites and their own benefit. It is a bit like losing your virginity: you are different, once you realize this. And with that kind of knowledge, you are more willing to be critical, regarding publicly presented narratives. Therefore, I am at least willing to entertain the proposition that our political leadership is not necessarily benevolent and that powerful forces backstage try to get their will.